Menumbuhkan Budaya Menulis melalui Pelatihan Artikel Ilmiah di Kalangan Guru Madrasah Ibtidaiyah Swasta Darul Dakwah wal-Irsyad Lapeo, Sulawesi Barat - Meryta Febrilian Fatimah; Hirman Rachman; Laila Qadrini (Faculty of Engineering, Universitas Semarang, 2024)
The role of teachers in the world of education is crucial in developing student's collaborative intelligence. The ability to write scientific articles can help teachers contribute more to disseminating their knowledge and experience. This program is designed to improve teacher's skills in writing scientific articles through the introduction of basic concepts and effective writing practices. The participants in this program are 14 teachers from Madrasah Ibtidaiyah Swasta Darul Dakwah wal-Irsyad Lapeo (MIS DDI Lapeo). The method of this program consists of the theory session and the practice session. The theory session discusses the basic elements of scientific writing, including article structure, use of references, writing ethics, and good writing techniques. Furthermore, practical sessions provide opportunities for teachers from MIS DDI Lapeo to apply the knowledge they have gained with direct guidance. Program evaluation is carried out through pre-tests and post-tests to measure the increase in participant's understanding and skills. Through this activity, teachers from MIS DDI Lapeo experienced an improvement in understanding scientific writing, as well as an enhancement in practical skills in structuring and writing high-quality scientific articles.